Telaah Linguistik Historis Komparatif terhadap Bahasa Indonesia, Jawa, Madura, dan Bali - Mytha Candria (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
This article presents a comparative historical-linguistic study of four languages living in Indonesian archipelago, and the four languages investigated are Indonesian, Javanese, Madurese, and Balinese. These so-called nusantara languages are compared and contrasted so as to discover their similarities and differences, and the results of which reveal that they are of Austronesian language family.